The Correlation Between Obesity with Stroke Incidence among Elderly - Zubaidi, Alfan; Akbar, Muh. Syaiful (GLOBAL HEALTH SCIENCE GROUP, 2023)
Obesity can increase the risk of hemorrhagic stroke through increased blood pressure, tendency to blood clots, and systemic inflammation. The purpose of the study was to determine the relationship between the incidence of obesity and the increased risk of stroke in Karanganyar, Central Java. This was a cross-sectional study by applying non-probability sampling techniques by means of Consecutive Sampling. The instruments and study materials used in this study came from primary and secondary data, namely body scales and manual height measurements, Medical Records. The results showed that there was a relationship between obesity and the incidence of stroke in Karanganyar, Central Java (p=0.001). This study conclude that obesity have a close relationship with stroke. The policy about prevent obesity by healthy lifestyle need to be increases so it can help minimize the risk of stroke.